Rapid screening of 15 highly toxic pesticide residues in Angelica sinensis decoctions by thermal desorption electrospray ionization mass spectrometry - Hongyan Zhang; Qiaoying Chang; Xingzhi Wang; Jian Li; Guoyu Qiu; Fuxiang Wu; Renyuan Zhu; Ming Su (Food and Agricultural Immunology, 2022)
A decoction is the most common form of Chinese herbal medicine dosing. An Angelica sinensis decoction was qualitatively and semi-quantitatively analyzed for 15 highly toxic pesticide residues by thermal desorption electrospray ionization mass spectrometry (TD-ESI/MS) with a triple quadrupole mass spectrometer in multiple reaction monitoring mode without pretreatment. The instrument response was optimal and sensitivity was highest with the following parameters: thermal desorption temperature, 300 °C; 0.1% formic acid aqueous solution-methanol (1:1,V:V) solvent; syringe pump flow rate, 150 μL/h; and sampler length, 5 cm. Good linearity was attained within the appropriate linear range with the detection limits ranging from 0.01–0.05 mg/L. The same positive sample was verified for QuEChERS pretreatment coupled with liquid chromatography tandem mass spectrometry, showing good agreement with TD-ESI/MS. The newly developed method was demonstrated to be a rapid, green, and efficient analytical method for screening 15 highly toxic pesticide residues in Angelica sinensis decoctions.